STUDY ON GENETIC DIVERGENCE IN SESAME (SESAMUM INDICUM L.) GERMPLASM BASED ON MORPHOLOGICAL AND QUALITY TRAITS - TRIPATHI, ANJAY; BISEN, RAJANI; P. AHIRWAL, RAVINDRA; PAROHA, SEEMA; SAHU , ROSHNI (The Bioscan, 2013)
The evaluation of phenotypic variability, heritability, genetic advance and diversity in germplasm collections is important for both plant breeders and germplasm curators to optimize the use of the variability available. A total of 100 sesame accessions collected from diverse ecologies of India were used in this research work. Analysis of variance revealed significant difference among genotypes for all the nine characters studied. High heritability combined with high genetic advance was recorded for seed yield/plant, number of secondary branches/plant and 1000 seed weight indicating that these characters are controlled by additive gene effect and phenotypic selection of these characters would be effective for further breeding purpose.Genetic divergence using Mahalanobis D2 statistics was worked out and based on D2 values the germplasm lines were grouped into eleven different clusters. Clustering was not associated with the geographical distribution instead accessions were mainly grouped due to their morphological differences. Maximum inter cluster distance was observed between cluster VI and cluster XI (134.72) followed by clusters V and XI (124.23) while, lowest divergence was noticed between cluster IV and V (9.37). Among the nine characters studied, days to 50% flowering contributed highest towards genetic divergence (21.05 %) followed by seed yield per plant (20.85 %). Cluster VI exhibited highest means for days to 50 % flowering (62.5), plant height (119.8), number of primary and secondary branches per plant (10.4, 19.3) and days to maturity (110.5). Cluster XI exhibited lowest means for days to 50 % flowering (46), plant height (81.4), number of primary branches per plant (6.7) and days to maturity (100.5). Greater genetic divergence was found between clusters VI and XI followed by clusters V and XI indicating superior and novel recombinants and explore the fullest range of variability for the characters and to realize good recombinant can be realized by mating between the lines of these clusters in a definite fashion.